ANALISIS FAKTOR YANG MEMPENGARUHI KINERJA EKSPOR INDONESIA - Adrian D. Lubis (Buletin Ilmiah Litbang Perdagangan, 2010)
Price and gross domestic product are always use as variables to predict the Indonesian export performance, and it is assumpted that aggragate price and gross domestic product will change 30 to 70 percent it’s performance. This study will build new another assumption to predict the Indonesian export performance. This study use multiregression analysist, and found that Indonesia export tiedly dependent on ten major partners. They are Australia, China, france, germany, Japan, Korea Rep., Malaysia, Thailand, united Kingdom and united States. Indonesia export performance to those partners is influenced by fluctuation of their GDP per capita. This study also found that the Indonesia export performance for agricultural and industrial goods in general depend on fluctuation of comodity price, gdp per capita, and real exchange rate.